Penerapan Universal Precaution pada Masyarakat dalam Pemutusan Rantai Penularan Infeksi Covid-19 - Esi Afriyanti; Elvi Oktarina; Leni Merdawati (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2021)
Covid-19 is an infectious disease that originated in Wuhan, China. Covid-19 is a pandemic that has hit almost all countries in the world. Indonesia itself has not been spared the Covid-19 pandemic. Preventive efforts are the key to implementation in the health sector and community services in order to prevent the spread of Covid-19 infection. The most effective prevention efforts in the community are universal precautions. The implementation of the Universal Precaution that is easy to do is by habituation of hand hygiene using hand sanitizer and the application of correct cough etiquette. The method used in this service activity was the community educated method included demontration, watching related videos and training that involves the community in the work area of ​​the Puskesmas Alai as a Health Center. Followed by providing booklets which were one means to increase public knowledge about proper hand washing and cough etiquette. With the provision and distribution of booklets after the counseling, it is hoped that information on hand washing and cough etiquette will be conveyed systematically.